Elementary school science and how to teach it - Blough, Glenn Orlando; Schwartz, Julius (Fort Worth : Holt, 1990)
This book is divided into four parts: Teaching elementary school science; The earth and the universe; Living things; and Matter and energy.
Keywords: Education; Science; Primary Education; Scientific study; Scientific teaching; Science -- Study and teaching (Primary) -- United States